Student as a player – projecting didactic tools in early art education and academic education - KARCZMARZYK, Małgorzata; BANASIAK, Małgorzata (Journal of Education, Technology and Computer Science, 2014)
The modern student is privately a player. He/she spends hours sitting at the computer and experiencing many positive feelings such as joy, surprise, curiosity, excitement. Is there anything more exciting than the adventure in a virtual world and at the game? In our presentation we will try to provide an educational game as an interesting opportunity to teach and study early school children and the students – future teachers. Projecting educational games (both board and computer ones) and testing them, can be a wonderful way to develop students’ interests and to learn and study in an interesting way. We will present our projects conducted with the students of the University of Gdansk, of Gdansk Higher School “Athenaeum”, and of the Nicolaus Copernicus University in Torun, which may provide inspiration for educational and teaching activities of other teachers and show that science can also be interesting and adventurous.